Upaya Guru Al-Qur`An Hadits dalam Meningkatkan Kemampuan Baca Al-Quran Peserta Didik di Mts Al-Khaeriyah NW Pare Kecamatan Praya Timur: Efforts of Al-Qur'an Hadith Teachers to Improve Students' Al-Qur'an Reading Skills at MTs Al-Khaeriyah NW Pare, Praya Timur District - Muhammad Hanafi (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
The sources of religious education are the Qur'an and the Hadith. The Qur'an holds the primary position for drawing upon other educational references. The Qur'an's universality encompasses all existing knowledge. The purpose of this study is to determine the efforts of Al-Qur`an Hadith teachers, supporting and inhibiting factors in improving the ability to read the Al-Qur`an of students. This type of research is qualitative research, while the data collection techniques include: interviews, observation and documentation, then researchers analyze to obtain the results of the study. The results of the research and analysis concluded that the supporting factors of Al-Qur`an Hadith teachers in improving the ability to read the Al-Qur`an are, the existence of extracurricular activities of tahfidz qur'an and adequate facilities and infrastructure. The factors that become obstacles are, there are still students who have not been able to read the Al-Qur`an, and the efforts of Al-Qur`an Hadith teachers in improving the ability to read the Al-Qur`an are, providing motivational injections, approaching, habituating Al-Qur`an tadarrus to students at each hour of Al-Qur`an Hadith lessons begin, and giving assignments/homework in the form of memorizing surahs related to the material discussed at each meeting.